1985
DOI: 10.1111/j.1471-0528.1985.tb04872.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal response to electrocautery of the ovary in patients with polycystic ovarian disease

Abstract: Fifty-eight women with polycystic ovarian syndrome (PCO) were treated with electrocautery of the ovarian capsule and then studied by hormone analysis for 12 months. In 72% ovulation appeared to occur within 4 weeks and in this group mean serum LH and FSH levels showed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(27 citation statements)
references
References 20 publications
3
22
0
2
Order By: Relevance
“…Consecutively, the peripheral conversion of androgens to oestrogens should be lowered, resulting in a correction of LH hypersecretion on the pituitary level [48]. Furthermore, lower androgen shall convert the intraovarian androgenic milieu to an oestrogenic one [49]. This mechanism shall diminish the atresia of chronically hyperandrogenic small follicles and restore normal follicular recruitment [50].…”
Section: Pathomechanismmentioning
confidence: 98%
“…Consecutively, the peripheral conversion of androgens to oestrogens should be lowered, resulting in a correction of LH hypersecretion on the pituitary level [48]. Furthermore, lower androgen shall convert the intraovarian androgenic milieu to an oestrogenic one [49]. This mechanism shall diminish the atresia of chronically hyperandrogenic small follicles and restore normal follicular recruitment [50].…”
Section: Pathomechanismmentioning
confidence: 98%
“…They sug gested that the decreased androgen levels may have removed an intraovarian block to follicular maturation. Gjonnaess et al [15] and Aakvaag and Gjonnaess [16] reported that the serum T levels dropped significantly in response to ovarian electrocautery and remained low in the ovulatores while T levels increased gradually and sig nificantly in the nonovulatores. Daniell and Miller [6] reported that physically opening the subcapsular cysts with the laser may temporarily lower the overall andro gen content of the ovaries and temporarily resolve the block to ovulation known to be associated with high intraovarian androgen levels.…”
Section: Discussionmentioning
confidence: 99%
“…One may speculate that the fall in the local T level would remove the block to follicular maturation and allow progression to ovulation. Furthermore, Aakvaag and Gjonnaess [ 16] theorized that ovarian cautery laparoscopically destroyed the inhibiting principal 'intraovar ian inhibitor' and thus allowed ovulation to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Die Operation führt zu einer Zerstörung ovariellen Gewebes mit einer konsekutiven Absenkung der intraovariellen Androgenproduktion und somit zu einer verringerten peripheren Konversion von Androgenen zu Östrogenen. Die endokrinen Veränderungen nach Thermokoagulation sollen das intraovarielle androgenbetonte Milieu bei PCOS hin zu einem östrogenbetonten Milieu verändern [9] und so einen chronischen androgenbedingten Stopp der Follikelreifung verhindern und ein normales follikuläres Recruitment erlauben [8] .…”
Section: Pathomechanismusunclassified